Флора прибрежно-водной полосы нижнего участка реки Днестр и её притоков на территории Республики Молдова [Articol] - Ерошенкова, Виктория (CEP USM, 2024)
Исследованный участок р. Днестр и его притоков представлен 113 видами, 103 родами из 55 семейств высших растений (Magnoliophyta). Наибольшим разнообразием характеризуются семейства сложноцветные (Asteraceae) 21 вида и злаковые (Poaceae) 8 видов. Около 1/3 из общего количества видов представлены Евразиатским элементом. Спонтанный элемент исследуемой флоры представлен 54 видами, а рудеральный 36 видами. Инвазивные элементы представлены видами Ailanthus altissima (Mill.) Swingle, Acer negundo L. Amorpha fruticosa L., Ambrosia artemisiifolia L.,Grindelia squarrosa Willd. Проводилось, также, для всех видов: определение процентного соотношения жизненных форм, биологических индексов, экологических групп по отношению к влажности, соотношение видов растений по происхождению, распределение видов-индикаторов по азоту (N) в процентном соотношении и соотношение видов растений по отношению к категории трофности.

The studied section of the river. The Dniester and its tributaries are represented by 113 species, 103 genera from 55 families of higher plants (Magnoliophyta). The greatest diversity is found in the Asteraceae (21 species) and Poaceae (8 species) families. About 1/3 of the total number of species are represented by the Eurasian element. The spontaneous element of the studied flora is represented by 54 species, and the ruderal element by 36 species. Invasive elements are represented by the species Ailanthus altissima (Mill.) Swingle, Acer negundo L. Amorpha fruticosa L., Ambrosia artemisiifolia L., Grindelia squarrosa Willd.. It was also carried out for all species: determination of the percentage ratio of life forms, biological indices, ecological groups in relation to humidity, the ratio of plant species by origin, the distribution of indicator species by nitrogen (N) in percentage terms and the ratio of plant species in relation to the category trophicity.
Flora of the riverside-water side of the lower section of the Dniest river and its tributaries on the territory of the Republic of Moldova
Keywords: флора; вид; семейство; flora; species; family